OPTIMALISASI METODE MUROJA’AH DALAM PROGRAM TAHFIDZ AL-QUR’AN DI SMAN 9 REJANGLEBONG - Ibrahim Rasulil Azmi (IAIN Bengkulu, 2019)
The purpose of the research in writing this thesis is to analyze: 1) the process of optimization of the method of Muroja’ah in the Tahfidz Al-Qur’an Program at SMAN 9 RejangLebong. 2) factors that support and hinder the implementation of the Tahfidz Qur’an Program at SMAN 9 RejangLebong. This thesis is useful so that it can become a reference for taking policies that can improve the memorization quality of SMAN 9 RejangLebong students. Future researchers are expected to become foothold in the formulation of advanced research designs that are deeper and more profound comprehensive especially with regard to research on development the method of muraja’ah in memorizing and maintaining memorization of the Qur’an. The research method used is qualitative research. In collecting data using the method of observation, in-depth interviews and documentation, using analysis of data reduction, data presentation and verification. This study also checks the validity of the data by using the techniques of credibility, confirmability, transferability, and dependenbility. The results of the study reveal that: 1) Process of Optimizing the Murajaah Method in the Tahfidz Quran program at SMAN 9 RejangLebong. i.e. by using the 1 day 1 paragraph system has succeeded with a minimum standard of 75% Where a teacher or student who is appointed can read the next verse capable of repeating the other students, then repeated when, praying duha, resting hours, prayer prayer hours, at home with the help of parents, and at home written again. The next day told randomly lead murajaah so that every student is ready and memorized. In the process of memorizing the Qur’an, of course, there must be sincere intentions, support from parents, having a big and strong determination, istiqomah, and fluently reading the Qur’an. 2) the application of the muraja’ah method in memorizing the Koran Case Study at SMAN 9 RejangLebong, which is supported by several activities of muraja’ah memorization, among others, is the deposit (memuraja’ah) new memorization to the teacher / colleague, Muraja’ah memorization the old one who was listened to by a friend faced two people two people, Muraja’ah memorized a long time to the teacher and students who were appointed (recitation test). In applying a method that is used, namely muraja’ah recitation of the Qur’an, of course there are inhibiting factors in the implementation of the optimization of the muraja’ah method in memorizing the Qur’an in theRejanglebongsman 9, namely: verses that have been memorized forget again, lazy, exhausted, a little time, limited tahfidz teacher, less active parents, and less supportive environment and environment.